PENGARUH KEPEMIMPINAN, IKLIM ORGANISASI, DAN KEPUASAN KERJA TERHADAP KINERJA - Faisal, Ahmad; Lestari, Kartika Dian (Feb Universitas Dirgantara Marsekal Suryadarma, 2019)
This study aims to obtain facts, data and information, valid and true, and can be trusted about the influence of Leadership, Organizational Climate, Job Satisfaction on Teacher Performance, at Raflesia Foundation Depok.Data derived from questionnaires distributed were analyzed data, among others: description of data, testing of research requirements, including normality test, homogeneity test, and linearity test. To prove the influence of variables of Leadership (X1), Organizational Climate (X2) and Job Satisfaction (X3) on Performance (Y) in this research, used data analysis technique with path analysis.Based on result of research analysis: 1) There is an influence of Leadership (X1) to Job Satisfaction (X3) 0,601; 2) There is an influence of Organizational Climate (X2) to Job Satisfaction (X3) equal to 0,283; 3) There is influence of Perception About Leadership (X1) to Performance (Y) equal to 0,310; 4) There is an effect of Organizational Climate (X2) on Performance (Y) of 0.251; 5) There is influence of Job Satisfaction (X3) on Performance (Y) of 0.366